TINJAUAN ISU-ISU YANG MEMBATASKAN PENGGUNAAN WAKAF DALAM PEMBANGUNAN EKONOMI UMMAH DI MALAYSIA - Shakrani, Mohd Saharudin (Jurnal Syariah, 2019)
Waqf is one of the Islamic instituti(l’l:) that combine spiritual and material element in economic development. It is a balanced development institution that is important for developing economics of ummah. This is based on history for its role in developing ummah in the countries such as Egypt, Turkey, Saudi Arabia and Kuwait. In Malaysia, the waqf institution is not functioning very well in improving economics well being of ummah. The focus of this study is to examine the preliminary issues that restrict the proper implementation of waqf in economic planning in Malaysia. Firstly, the issue is on the problem in clarification on how to develop the waqf according to the Islamic scholar’s opinion. Secondly, the issue is on the legislation obstacles, and the third issue is on the problem of Baitul Mal’s administration that is inefficient and unsystematic.